Structural and Electrophysiological Changes in a Model of Cardiotoxicity Induced by Anthracycline Combined With Trastuzumab - Altomare, Claudia; Lodrini, Alessandra Maria; Milano, Giuseppina; Biemmi, Vanessa; Lazzarini, Edoardo; Bolis, Sara; Pernigoni, Nicolò; Torre, Eleonora; Arici, Martina; Ferrandi, Mara; Barile, Lucio; Rocchetti, Marcella; et al. (Frontiers in Physiology, 2021)
Background: Combined treatment with anthracyclines (e.g., doxorubicin; Dox) and trastuzumab (Trz), a humanized anti-human epidermal growth factor receptor 2 (HER2; ErbB2) antibody, in patients with HER2-positive cancer is limited by cardiotoxicity, as manifested by contractile dysfunction and arrhythmia. The respective roles of the two agents in the cardiotoxicity of the combined therapy are incompletely understood. Objective: To assess cardiac performance, T-tubule organization, electrophysiological changes and intracellular Ca2+ handling in cardiac myocytes using an in vivo rat model of Dox/Trz-related cardiotoxicity. Methods and Results: Adult rats received 6 doses of either Dox or Trz, or the two agents sequentially. Dox-mediated left ventricular (LV) dysfunction was aggravated by Trz administration. Dox treatment, but not Trz, induced T-tubule disarray. Moreover, Dox, but not Trz monotherapy, induced prolonged action potential duration (APD), increased incidence of delayed afterdepolarizations (DADs) and beat-to-beat variability of repolarization (BVR), and slower Ca2+ transient decay. Although APD, DADs, BVR and Ca2+ transient decay recovered over time after the cessation of Dox treatment, subsequent Trz administration exacerbated these abnormalities. Trz, but not Dox, reduced Ca2+ transient amplitude and SR Ca2+ content. Both agents increased Ca2+ waves and downregulated SERCA. Finally, Dox increased resting Ca2+ waves, Ca2+ spark frequency, spark-mediated sarcoplasmic reticulum (SR) leak, and long-lasting Ca2+ release events (so-called Ca2+ “embers”). Conclusions: These results suggest that Dox, but not Trz, may cause T-tubule disarray in cardiac myocytes in vivo while also inducing overall larger changes in electrical parameters and intracellular Ca2+ handling. While Dox-induced changes in electrical parameters are reversible, subsequent Trz administration prevents their recovery. These findings illustrate the specific roles of Dox and Trz, and their interactions in cardiotoxicity and arrhythmogenicity.